Russian Universities’ Further Education: Integration with International Markets - Ilya A. Korshunov (National Research Mordova State University, 2018)
Introduction. The paper describes the role of Russian transnational corporations in the development and implementation of the Adults’ Education and Vocational Education and Trainings programs in foreign countries as the promotion of Russian technologies. As the competition between the universities in the international educational markets rises, they see the increasing need for the fixation of the programs they offer onto the needs of the global companies, broadening the possibilities for the students to obtain relevant qualifications and skills, and corresponding diversification of educational programs. Among the possible directions for the increase in the educational services that are offered for export could be adults’ educational programs, vocational education and trainings. Materials and Methods. The study of the additional vocational education programs for foreign students was carried out with specialized questionnaire. 180 higher education institutions took part in the survey. The analysis of the corporate segment of additional professional education services for foreign markets was carried out on the basis of semi-formalized in-depth expert interviews. Results. Based on the collected empirical data we were able to identify main participants of the Adults’ Education and Vocational Education and Trainings export and structure and spheres of the programs as well as target countries in this market in three years’ time. It was revealed that the most successful providers of the educational programs are the universities that on the one hand offer already well developed and sought-after educational programs on the Russian Adults’ Education and Vocational Education and Trainings market, and on the other hand – already have stable partnership ties with countries that send students to undergraduate programs. Discussion and Conclusion. This study elaborates on the role of universities in promoting competitive technologies through the distribution of Adults’ Education and Vocational Education and Trainings. Mechanisms for formation and implementation of corporate training programs by universities for Russian industrial corporations are structured. Barriers for the attraction of foreign students are discussed to increase the scope of training. Results of the study can be recommended for the universities concerned with the development of the Adults’ Education and Vocational Education and Trainings sector in the international context.